Agro-hydrologic modelling for simulating soil moisture dynamics in the root zone of Potato based on crop coefficient approach under limited climatic data. (1st November 2022) - Kumar, Navsal; Shankar, Vijay; Poddar, Arunava
ABSTRACT: Field lysimetric experiments were conducted on Potato crop grown in a humid sub-tropical agro-climate during 2014–2017 cropping seasons. Reference evapotranspiration (ET0 ) methods based on limited climatic data were evaluated with the FAO-56 Penman-Monteith (P-M) method. The performance of temperature-based and radiation-based methods was reliable, but evaporation-based methods performed poorly. The best methods in each category viz. Hargreaves-Samani, FAO-24 Radiation, and Snyder along with FAO-56 P-M were considered to estimate the empirical crop evapotranspiration (ETc ) using the crop coefficient approach. The empirical ETc was compared with the field ETc obtained through water balance approach. A root water uptake-based numerical model was utilized to simulate the soil moisture dynamics in the crop root zone, wherein ETc is an important input parameter. The model simulated soil moisture was compared with the field observed values. Results indicate that FAO-56 P-M and Hargreaves-Samani-based simulated values presented close agreement with field observed values. FAO-24 Radiation and Snyder-based simulations underestimated and overestimated the field observed soil moisture, respectively. The field soil moisture depletion of 30% corresponds to simulated depletion of 15% (Snyder), 25% (Hargreaves-Samani), 28% (FAO-56 P-M) and 40% (FAO-24 Radiation).